SOCIAL IMPACTS OF DIGITAL DEVICES USED FOR FOSTER CHILDREN IN LEMBAGA PEMBINAAN KHUSUS ANAK KELAS 2 JAKARTA - Edgar Refansyah; Nadia Yovani (Lafadz Jaya Publisher, 2023)
Children have the right to education throughout their lives, regardless of their status. In this study, we will analyze the social benefits of using digital technology for foster children, and how the DKI Jakarta Special Development Institute for Children (LPKA) class 2 can meet these needs. Previous research that is used as a reference is research with the theme of the rights of children in conflict with the law and research with the theme of the digital skills gap for adolescents. The weakness in previous research is that there are no results that explore how the social benefits obtained by foster children from using digital technology and how LPKA can provide access to digital technology for them. This research uses a descriptive method complemented by qualitative data with purposive sampling. Interviews were conducted with eight selected foster children from the DKI Jakarta Special Development Institute for Children (LPKA) class 2. The findings of this study are the social benefits of using digital technology owned by LPKA Class 2 Jakarta foster children in the form of the ability to interact at a distance, the ability to deepen skills, and the ability to sort information. The conclusion of this study is that digital technology that can be accessed by prisoners can provide several sociological benefits and is used by them while undergoing a period of guidance.